Modern weapons and military equipment for issue 4/2013 - Vučković, Dragan M. (Vojnotehnički glasnik / Military Technical Courier, 2013)
Russia promotes a system to restrict accessAn unmanned ground vehiclesSukhoi T-50 programme still a work in progressRussian Air Force receiving upgraded A-50U AEW&C aircraftNetwork Space Surveillance and TrackingWarming trendThe new technologies of communication between aircraftMixed bag of SAMs